2017
DOI: 10.1902/jop.2016.160370
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Frequent Recreational Cannabis (Marijuana and Hashish) Use and Periodontitis in Adults in the United States: National Health and Nutrition Examination Survey 2011 to 2012

Abstract: FRC use is associated with deeper PDs, more clinical AL, and higher odds of having severe periodontitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
85
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(90 citation statements)
references
References 16 publications
3
85
0
2
Order By: Relevance
“…All studies included in this systematic review, with the exception of López’ study, presents an elevated prevalence of periodontal disease associated with marijuana use was found. Data related to review question on overall sample in Lopez and Baelum study were not available, once the authors showed a stratified analysis by time of marijuana use and frequency of smoking.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…All studies included in this systematic review, with the exception of López’ study, presents an elevated prevalence of periodontal disease associated with marijuana use was found. Data related to review question on overall sample in Lopez and Baelum study were not available, once the authors showed a stratified analysis by time of marijuana use and frequency of smoking.…”
Section: Discussionmentioning
confidence: 95%
“…Different criteria were adopted in the studies. The CDC/AAP (Center for Disease Control and Prevention/American Academy of Periodontology) was used in three studies . The others used the presence of clinical attachment loss ≥3 mm and ≥1 site with attachment loss ≥5 mm .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations